2018
DOI: 10.1038/s41598-018-34082-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulations of Thrombolytic Therapy in Acute Ischaemic Stroke

Abstract: Ischaemic stroke can occur when an artery to the brain is blocked by a blood clot. The use of thrombolytic agents, such as tissue plasminogen activator (tPA), to dissolve the occluding clot is limited by the risk of intracerebral haemorrhage (ICH), a known side effect associated with tPA. We developed a computational thrombolysis model for a 3D patient-specific artery coupled with a compartmental model for temporal concentrations of tPA and lysis proteins during intravenous infusion of tPA, in order to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 58 publications
7
61
0
Order By: Relevance
“…To the best of our knowledge, only two computational studies have attempted to include both the systemic effects of tPA via PK modelling and clot lysis dynamics [19,20]. Anand and Diamond [19], by combining a one-compartment model for the systemic circulation of tPA and a one-dimensional (1D) clot lysis model to simulate thrombolytic therapy for the treatment of AMI, developed a computational model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only two computational studies have attempted to include both the systemic effects of tPA via PK modelling and clot lysis dynamics [19,20]. Anand and Diamond [19], by combining a one-compartment model for the systemic circulation of tPA and a one-dimensional (1D) clot lysis model to simulate thrombolytic therapy for the treatment of AMI, developed a computational model.…”
Section: Introductionmentioning
confidence: 99%
“…Their model provides a good foundation for a computational study of fibrinolysis and it accounts for crucial fibrinolytic proteins, although the description of fibrinolysis as a continuous shrinkage of fibre diameter seems unrealistic as fibrin fibres are cut transversely during fibrinolysis [21]. A more recent three-dimensional (3D) patient-specific model has been developed by Piebalgs et al [20], which couples a one-compartment model and a fibrinolysis model that is based on the degradation of fibrin binding sites in the clot rather than fibre shrinkage. By using a multiscale modelling approach, the biochemical reactions of fibrinolysis are integrated with macroscale blood flow and drug transport in a 3D patient-specific model to assess the effects of different tPA doses on the outcome of thrombolytic therapy for AIS and the risk of ICH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation of fibrinolysis in a 3D patient-specific artery during thrombolytic therapy showed that clot lysis was accelerated at higher tPA doses at the expense of a substantial increase in the risk of intracerebral hemorrhage, which was supposed to be associated with fibrinogen consumption. 104 Mathematical modeling in blood coagulation is a potent tool for investigation of mechanisms regulating different aspects of clotting, such as thrombin generation, clot dissolution, action of different drugs, used for hypo-and hypercoagulation correction, and for thrombolysis. Yet, the direct translation of in silico results to in vitro/ex vivo setups is apparently too premature and requires further investigations of clotting regulating parameters.…”
Section: Computer Models Of Blood Coagulation and Fibrinolysismentioning
confidence: 99%
“…The therapy involves the intravenous infusion of alteplase, to dissolve the clot. Although the treatment is critical it has a sever side effect, intracerebral hemorrhage (ICH) [27]. To simulate a thrombolytic treatment in our model, a blood clot was inserted, and occlusion of the vascular compartment was confirmed.…”
Section: Restoration Of Flow Via Thrombolysismentioning
confidence: 99%